Paralympischer Spitzensport und Inklusion - ein gangbarer Weg? - Innenmoser, J. (Leipziger Sportwissenschaftliche Beiträge, 2012)
With the start of the Paralympic Summer Games in London in August 2012 many athletes with disability from around the world will come together. The Games will lead them to new experiences and it is hoped that the performance of paralympic athletes will be broadly accepted. On the other hand many peo-ple believe, that the games will transport a new spirit into the life of people with disabilities. The 2006 UN-Convention on the rights of persons with disabilities is published and accepted by the states parties worldwide and it is hoped that it will take much more influences to the life of persons with and without disabili-ties. Perhaps it may also take influences to the ways how we are performing sport - in general - in the future. The idea "Inclusion" produces changes in all day living activities and also in the different forms of sport - if people are will-ing to accept. The chapters of the convention which are involved with sport practice are described and discussed in this paper, especially the ways of high-performance sport of persons with and without disabilities. Perhaps the games in London may not show new ways of inclusive sport but they will give a new drive to the changes of sport in clubs and in the school. Zusammenfassung Die im August beginnenden paralympischen Sommerspiele in London werden - auch wegen ihres hohen Erlebniswertes - erneut als Höhepunkt der Aner-kennung der sportlichen Leistungen behinderter Athleten erwartet. Fraglos auch erhofft man sich eine Aufwertung der Lebenssituation der Menschen mit Behinderungen in der gesamten Welt. Dieses allerdings will die UN-Behin-dertenrechts-Konvention von 2006 ebenfalls erwirken. Ihre wesentlichen Bestim-mungen werden dargelegt und es wird aufgezeigt, welche Forderungen auf den Sport übertragbar sind bzw. wie sich der Sport als Ganzes zu verändern hat. Im Vergleich zwischen dem Spitzensport der Menschen ohne Behinderungen und dem paralympischen Spitzensport wird klar, dass ein gemeinsames Training für die Idee Inklusion sehr nützlich wäre. Ob die beiden Wege der Durchführung des Sports aber bald dazu führen werden, dass es zu der erhofften Einheit der Sporttreibenden kommen wird, muss abgewartet werden.